Two new species of Halysioncum Caira, Marques, Jensen, Kuchta et Ivanov, 2013 (Cestoda, Diphyllidea) from Indo-Pacific rays of the genus Aetomylaeus Garman (Myliobatiformes, Myliobatidae) - Ivanov, Veronica Adriana (2013)
Abstract: Recent collections of cestode parasites from two species of the myliobatid genus Aetomylaeus Garman from several localities in the Pacific Ocean resulted in the discovery of two new species of Halysioncum Caira, Marques, Jensen, Kuchta et Ivanov, 2013. Halysioncum gibsoni sp. n. from Aetomylaeus maculatus (Gray) in the South China Sea off Borneo differs from all of its congeners in having the following combination of characters: 27 apical hooks (14 type A and 13 type B hooks), 11?12 lateral hooklets, 22?28 spines per column on the cephalic peduncle, testes distributed in a single column and an internal seminal vesicle. Halysioncum arafurense sp. n., recovered from Aetomylaeus cf. nichofii 2 (sensu Naylor et al. 2012b) in the Arafura Sea off the Wessel Islands, Northern Territory, Australia, can be distinguished from its congeners based on the following combination of characters: 23 apical hooks (12 type A and 11 type B hooks), the number of lateral hooklets (9?11), the number of spines per column on the cephalic peduncle (20?24), the number and distribution of the testes (13?15 testes in two irregular columns), and the distribution of vitelline follicles (interrupted dorsally at the level of the ovarian lobes). Both species represent the first verified records of diphyllideans from eagle rays of the genus Aetomylaeus and formally extend the host associations of diphyllideans to include a third genus of Myliobatiformes. The myliobatiforms are indeed an understudied group of available hosts for diphyllideans and represent interesting target hosts if the diversity of diphyllidean tapeworms is to be fully estimated and understood.